HUBUNGAN KESEJAHTERAAN KARYAWAN DENGAN LEVERAGE PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN INDEKS KOMPAS 100 DI BURSA EFEK INDONESIA) - , IDEL PATRIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is performed in order to obtain an empirical studies the relation of employee well-being and firm leverage on companies that listed in Kompas 100 Index Indonesian Stock Exchange (IDX) on period 2008-2012 The focus of this study is firms in all sector except financial sector that listed in Kompas 100 Indonesia Stock Exchange (IDX) during 2008 to 2012. One hundred and thirty six companies obtained as sampling. The method of sampling is purposive sampling. Data Analysis used linear regression panel data to test a relation each variable independent (employee well-being), control variable (total asset, profitability, price to book value, dividen paying behavior, tangibility, operating income volatility, asset growth) and dependent variable (firm leverage). The regression result showed no relation between independent variable (employee well-being) and dependent variable (firm leverage).